A Case of Bilateral Anesthesia Mumps after Cesarean Section under Spinal Anesthesia: A Rare Case and Literature Review - Narges Montazeri; Mohammad Hassan Darabi; Kamran Hessami; Ramin Shekouhi; Maryam Sohooli; Tahereh Shamsi; Fateme Bagheri; Mohammad Amin Shahrbaf (Case Reports in Obstetrics and Gynecology)
A 30-year-old pregnant female presented to the emergency department with labor pain in her 39th week of pregnancy. Cesarean section under spinal anesthesia was the chosen route of delivery for this patient due to previous cesarean section in her first pregnancy. The delivery itself was uneventful but seven hours after the surgery, bilateral swelling of parotid glands were noted. Rehydration therapy and a single dose of hydrocortisone (100 mg IV route) were administered, and swellings were completely resolved on postoperative day 2. This is one of the rare cases of anesthesia mumps after spinal anesthesia, and we think rehydration therapy and the single dose corticosteroid may prove useful in these cases.